2018
DOI: 10.1063/1.5031181
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of harmonic distortions in photovoltaic integrated industrial microgrid

Abstract: Due to the abundance of power electronic appliances, harmonic distortion has become one of the growing power quality concerns in recent years. Harmonic distortion is also caused by the nonlinearity of other power equipment such as transformers and rotating machines. Power systems, rich in harmonics, offer poor power factor and hence low efficiency operation. Due to the large concentration of nonlinear loads such as motor drives, investigation of harmonic distortion in industrial systems is getting special atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Consequently, Figure 5b presents a higher THD value than Figure 5e, confirming the fact that variations in the operation conditions have an impact on the resulting THD. On the other hand, it has been demonstrated that even slight variations in the operating conditions of the PV system may affect the harmonic distortion in the network [7]. This situation can be verified by performing a comparison between Figures 4 and 5; for instance, Figure 4b presents a day with variations in the irradiance conditions, whereas Figure 4e presents another day without sudden variations.…”
Section: Experimentation Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Consequently, Figure 5b presents a higher THD value than Figure 5e, confirming the fact that variations in the operation conditions have an impact on the resulting THD. On the other hand, it has been demonstrated that even slight variations in the operating conditions of the PV system may affect the harmonic distortion in the network [7]. This situation can be verified by performing a comparison between Figures 4 and 5; for instance, Figure 4b presents a day with variations in the irradiance conditions, whereas Figure 4e presents another day without sudden variations.…”
Section: Experimentation Resultsmentioning
confidence: 77%
“…Additionally, it has been reported that the inclusion of PV generation is associated with harmonic contamination [5,6], because it is necessary to use power inverters for converting the DC signals delivered by the PV panels into AC signals, which can be used by the final users. It is necessary to note that even small variations in the background conditions may lead to a severe harmonic contamination, making the constant detection of these variations essential [7]. From the smart grid point of view, these are major issues, as the variability makes the generation process unreliable, and the harmonic content compromises the quality of the power supply.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that the presence of PV on the network is sometimes considered as one of the harmonic distortion resources [6], in this paper, we try to utilize PV as a solution to reduce THD level. On the other hand, the main role of power electronic devices, which are utilized as interfaces for RES such as PVs, is providing the power with the required level of power quality.…”
Section: Nomenclature αmentioning
confidence: 99%
“…Accordingly, for any harmonic distortions, the extra cost called expected value of economic losses due to harmonics, could be calculated according to (5), and the harmonic distortion cost in each duration is determined in the form of On the other hand, to calculate the second objective, the cost of loss at the power frequency, according to the energy price in the network (π c ), is obtained from Eq. (6).…”
Section: R Bothmentioning
confidence: 99%
“…These problems primarily stem from the non-ideal characteristics of power electronic equipment. The power providers are warranted to ensure stable, smooth, and safe power supply conforming to a pure sinusoidal voltage signal to the end-user [2]. At present-day, with the worldwide energy crisis becoming increasingly conspicuous and environmental pollution becoming increasingly serious, worldwide renewable generation technologies have been developed rapidly [3][4][5].…”
Section: Introductionmentioning
confidence: 99%